Neonatal encephalopathy with a pungent body odour. Issue 1 (1st July 1997) - Walker, V; Mills, G A; Fortune, P-M; Wheeler, R
Abstract : A neonate had transient unexplained bleeding into the gut, severe encephalopathy, and an abnormal pungent body odour. An inherited metabolic defect was excluded. The malodour was due to methanethiol and hydrogen sulphide, identified in urine. These sulphur compounds may have contributed to encephalopathy. Colonic bacteria were the probable source.